2020
DOI: 10.1007/s11524-020-00441-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling COVID-19 and Its Impacts on U.S. Immigration and Customs Enforcement (ICE) Detention Facilities, 2020

Abstract: U.S. Immigration and Customs Enforcement (ICE) facilities house thousands of undocumented immigrants in environments discordant with the public health recommendations to reduce the transmission of 2019 novel coronavirus . Using ICE detainee population data obtained from the ICE Enforcement and Removal Operations (ERO) website as of March 2, 2020, we implemented a simple stochastic susceptibleexposed-infected-recovered model to estimate the rate of COVID-19 transmission within 111 ICE detention facilities and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 10 publications
0
38
0
2
Order By: Relevance
“…The probability that an interaction with an infected agent results in transmission of the infection is governed by β, which is 0.168206 for models with R0=2.6, 0.127852 for models with R0=2.0, and 0.22201 for models with R0=3.4. Results in this paper reflect R0=2.6, a commonly used value at this time, and results for a broader range of possible values, R0=2.0 and 3.4 (2,(24)(25)(26)(27), are presented in the Supplementary Materials.…”
Section: Corvid Agent-based Modelmentioning
confidence: 68%
“…The probability that an interaction with an infected agent results in transmission of the infection is governed by β, which is 0.168206 for models with R0=2.6, 0.127852 for models with R0=2.0, and 0.22201 for models with R0=3.4. Results in this paper reflect R0=2.6, a commonly used value at this time, and results for a broader range of possible values, R0=2.0 and 3.4 (2,(24)(25)(26)(27), are presented in the Supplementary Materials.…”
Section: Corvid Agent-based Modelmentioning
confidence: 68%
“…Preliminary analysis from Cook County Jail, IL shows that jail cycling was associated with 15.7% of documented cases in IL, exceeding other known predictors (e.g., population density and public transit utilization) (Reinhart & Chen, 2020). A simple stochastic susceptible exposedinfected-recovered model of COVID-19 disease spread in Immigration and Customs Enforcement detention centers shows that under optimistic conditions outbreaks among a minimum of 65 ICE facilities would overwhelm ICU beds within a 10-mile radius (Irvine et al, 2020). Additional epidemiologic modeling of ICE facilities indicates potential underreporting of cases (Siulc, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…A substantial number of studies were found to apply computeraided spatial and statistical analysis and modeling techniques in analyzing distinct aspects of COVID-19. A total of 16 articles were identified that emphasized on computer-aided spatial and statistical analysis and modeling in COVID-19 [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] . Most of these works were focused on analyzing the spatial distribution pattern of COVID-19 cases using the confirmed cases data [72][73][74][75][76][77][78] , or news reports of COVID-19 cases as proxy data 79 .…”
Section: Computer-aided Spatial and Statistical Analysis And Modelingmentioning
confidence: 99%